2004
DOI: 10.1073/pnas.0307476101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GAPDH as a protein target of the saframycin antiproliferative agents

Abstract: Saframycin A (SafA) is a member of a class of natural products with potent antiproliferative effects in leukemia-and tumor-derived cells. This activity is frequently conjectured to derive from the ability of saframycins to covalently modify duplex DNA. We used a DNA-linked affinity purification technique to identify GAPDH as a protein target of DNA-small molecule adducts of several members of the saframycin class. Nuclear translocation of GAPDH occurs upon treatment of cancer cells with saframycins, and deplet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 27 publications
2
38
0
2
Order By: Relevance
“…Nevertheless, such activity alone would be unlikely to account for the antimigratory activity of DX-52-1 or HUK-921 because other DNA-alkylating agents such as saframycin C (18), another reactive tetrahydroisoquinoline, and mitomycin C (8) do not inhibit cell migration during wound closure by MDCK cell sheets. Interestingly, covalent DNA-saframycin C adducts bind glyceraldehyde-3-phosphate dehydrogenase, and this appears to be involved in the mechanism of the antiproliferative activity of saframycin C (55). The data presented here extend the notion that reactive tetrahydroisoquinolines possess important protein targets and that their cellular activities may not be confined to or even principally result from any targeting of DNA.…”
Section: Discussionsupporting
confidence: 63%
“…Nevertheless, such activity alone would be unlikely to account for the antimigratory activity of DX-52-1 or HUK-921 because other DNA-alkylating agents such as saframycin C (18), another reactive tetrahydroisoquinoline, and mitomycin C (8) do not inhibit cell migration during wound closure by MDCK cell sheets. Interestingly, covalent DNA-saframycin C adducts bind glyceraldehyde-3-phosphate dehydrogenase, and this appears to be involved in the mechanism of the antiproliferative activity of saframycin C (55). The data presented here extend the notion that reactive tetrahydroisoquinolines possess important protein targets and that their cellular activities may not be confined to or even principally result from any targeting of DNA.…”
Section: Discussionsupporting
confidence: 63%
“…This intermediate has been implicated in the formation of covalent bonds with DNA. [23][24][25][26] The complex structure of the ecteinascidins is usually deconvoluted into three parts. Both subunits A and B represent the two tetrahydroisoquinoline rings forming the characteristic pentacycles resembling the saframycin-renieramycin framework.…”
mentioning
confidence: 99%
“…However, a more recent study documented that nitric oxide can also induce nuclear localization of GAPDH where it is acetylated by the acetyltransferase p300/CBP via direct protein interaction, which in turn causes stimulation of the catalytic activity of p300/CBP, resulting in the activation of downstream targets such as p53 (11). Other studies have shown that GAPDH is associated with DNA-containing genotoxic lesions such as thioguanylated DNA generated by the chemotherapeutic agent mercaptopurine used for treating acute lymphoblastic leukemia (12,13). Thus, it seems that GAPDH response to oxidative stress might be linked to a role in maintaining the integrity of the genome.…”
mentioning
confidence: 99%